2018
DOI: 10.1038/s41598-018-25824-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of chikungunya virus DNA using two-dimensional MoS2 nanosheets based disposable biosensor

Abstract: Development of platforms for a reliable, rapid, sensitive and selective detection of chikungunya virus (CHIGV) is the need of the hour in developing countries. To the best of our knowledge, there are no reports available for the electrochemical detection of CHIGVDNA. Therefore, we aim at developing a biosensor based on molybdenum disulphide nanosheets (MoS2 NSs) for the point-of-care diagnosis of CHIGV. Briefly, MoS2 NSs were synthesized by chemical route and characterized using scanning electron microscopy, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(43 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…Furthermore, the ability to detect vector-borne diseases (such as Zika virus [128], Dengue virus [129], chikungunya [130], and yellow fever virus [131]) directly from crude human sample matrices (blood, urine and saliva) with a smartphone-based diagnostic platform demonstrates the possibility of a widespread clinical deployment [132] at home or at a (off-grid) emergency shelter.…”
Section: Biometric and Medical Iot Applicationsmentioning
confidence: 99%
“…Furthermore, the ability to detect vector-borne diseases (such as Zika virus [128], Dengue virus [129], chikungunya [130], and yellow fever virus [131]) directly from crude human sample matrices (blood, urine and saliva) with a smartphone-based diagnostic platform demonstrates the possibility of a widespread clinical deployment [132] at home or at a (off-grid) emergency shelter.…”
Section: Biometric and Medical Iot Applicationsmentioning
confidence: 99%
“…The hybrid nanosheet containing 3DG-Au nanoparticles (Au NPs) provides a high surface area for immobilizing recognition probe and improved performance of the developed biosensor. Singhal et al applied methylene blue as a redox indicator for detection of chikungunya virus DNA [174]. For instance, nanostructured ZnO based DNA biosensor is fabricated for detection of bacterial meningitis [169].…”
Section: Electrochemical Genosensor For Detection Of Microorganismmentioning
confidence: 99%
“…As the representative TMDC, MoS 2 shows a high carrier mobility (60 cm 2 /V s at 250 K), a layer-dependent bandgap (1.2-1.8 eV), a high transistor on/off ratio (~ 10 8 ), and reasonable environmental stability [11]. Recent reports have demonstrated that 2D MoS 2 is a desirable channel material in FET sensor with breakthroughs in sensing performance for various analytes including NO 2 [12][13][14][15], NH 3 [16,17], chemical vapor [18,19], metal ion [20][21][22], small molecule [23][24][25], as well as biomaterials such as nucleic acid [26][27][28][29], protein [30][31][32], and microorganism [33]. Compared with MOSFET sensors, 2D-TMDCbased FET sensors normally show higher sensitivities due to the 2D nanosheet structure of TMDC.…”
Section: Introductionmentioning
confidence: 99%